IOT Enabled Carbon Dioxide and Carbon Monoxide Monitoring and Control for Vehicles to Reduce Air Pollution - G, Harikrishnegowda; K, Kavyashree; G, Jayakumar; S, Supriya R; N S, Chetan Kumar (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2017)
With rise in the amount of heat trapping gases the earth is getting warmer day by day, leading to global warming. CO2 and CO is the major contributor of the greenhouse gases. The main aim of this project is to reduce the greenhouse effect by real time monitoring and controlling of CO2 and CO emission caused due to vehicles and industries using IOT. The Internet of Things (IOT) extends internet connectivity to a diverse range of devices and everyday things that utilize embedded technology to communicate and interact with the external environment, all via the Internet. In this proposal, we have tried to make the CO2 and CO detector intelligent by saving the CO2 and CO levels in different regions. This model adheres to IOT and provides information for utilization of vehicular features based on the CO2 and CO levels. The model is cost effective and also can be easily produced and integrated with vehicles and also in industries.